2017
DOI: 10.1038/s41598-017-05222-2
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Early Life Stress on the Methylome and Transcriptome of Atlantic Salmon

Abstract: Exposure to environmental stressors during early-life stages can change the rate and timing of various developmental processes. Epigenetic marks affecting transcriptional regulation can be altered by such environmental stimuli. To assess how stress might affect the methylome and transcriptome in salmon, fish were treated using cold-shock and air-exposure from the eye-stage until start-feeding. The fish were either stressed prior to hatching (E), post-hatching (PH), pre- and post-hatching (EPH) or not stressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 69 publications
5
56
0
Order By: Relevance
“…The genes for collagens, myosin light‐chain kinase, dynein, zinc finger protein, 5‐hydroxytryptamine receptor and glutamate metabotropic receptor have been reported to be associated with morphological changes in the nervous, muscular and cardiovascular systems (Xu et al ., ). The GO and KEGG enrichment analyses showed that the significantly enriched GO terms were involved in DNA replication, metabolic process and enzyme activity, which are significant processes during fish embryogenesis (Moghadam et al ., ). Therefore, it is not surprising that the changes in allele frequencies in these genes affect the embryogenesis of C. idella and the survival of fish larvae; however, further studies are required.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The genes for collagens, myosin light‐chain kinase, dynein, zinc finger protein, 5‐hydroxytryptamine receptor and glutamate metabotropic receptor have been reported to be associated with morphological changes in the nervous, muscular and cardiovascular systems (Xu et al ., ). The GO and KEGG enrichment analyses showed that the significantly enriched GO terms were involved in DNA replication, metabolic process and enzyme activity, which are significant processes during fish embryogenesis (Moghadam et al ., ). Therefore, it is not surprising that the changes in allele frequencies in these genes affect the embryogenesis of C. idella and the survival of fish larvae; however, further studies are required.…”
Section: Discussionmentioning
confidence: 97%
“…The GO and KEGG enrichment analyses showed that the significantly enriched GO terms were involved in DNA replication, metabolic process and enzyme activity, which are significant processes during fish embryogenesis (Moghadam et al, 2017). Therefore, it is not surprising that the changes in allele frequencies in these genes affect the embryogenesis of C. idella and the survival of fish larvae; however, further studies are required.…”
Section: Pcr Confirmation Of the Changes In Allele And Genotype Frementioning
confidence: 99%
“…These gene regulation studies primarily use changes in DNA methylation as an indicator of ELS (Murgatroyd et al 2009, Kinnally et al 2011, Lewis & Olive 2014) and recent work has expanded these approaches into non-mammalian organisms (e.g. Rubenstein et al 2016, Moghadam et al 2017, Pértille et al 2017, Gott 2018, Sheldon et al 2018). DNA methylation studies of ELS investigate changes to the structure of DNA, but are often limited in the functional implications of ELS (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies have also taken candidate gene approaches to investigating gene expression in the context of ELS (Marco et al 2014, Diaz-Real et al 2017, Anastasiadi et al 2018, Reshetnikov et al 2018). However, very few studies assess genome-wide transcription under ELS (Moghadam et al 2017), particularly in the context of parental effects (but see: Weaver et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the quality of parental care can have strong impacts on offspring health resulting from epigenetic modifications (Liu et al, 1997;Meaney, 2001;Weaver et al, 2004). These gene regulation studies primarily use changes in DNA methylation as an indicator of ELS (Kinnally et al, 2011;Lewis & Olive, 2014;Murgatroyd et al, 2009) and recent work has expanded these approaches into nonmammalian organisms (e.g., Gott, 2018;Moghadam et al, 2017;Pértille et al, 2017;Rubenstein et al, 2016;Sheldon, Schrey, Ragsdale, & Griffith, 2018). DNA methylation studies of ELS investigate changes to the structure of DNA, but are often limited in the functional implications of ELS (i.e., transcription and translation).…”
mentioning
confidence: 99%